Modern drug self-medication and associated factors among pregnant women at Settat city, Morocco - Chergaoui, Samia; Changuiti, Omaima; Marfak, Abdelghafour; Saad, Elmadani; Hilali, Abderraouf; Youlyouz Marfak, Ibtissam (Frontiers in Pharmacology, 2022)
Purpose: The consumption of drugs during pregnancy without a medical advice, constitutes a risk for the mother and the fetus. It is a public health problem. this study assessed modern drug self-medication practice and associated factors among pregnant women attending health centers at Settat city in Morocco. Patients and methods: A cross-sectional study was conducted using a structured questionnaire on pregnant women who were attending Settat health centers. A simple random sampling technique was employed to select the study participants. Descriptive and inferential statistics were computed using the SPSS version 19. Results: Among 364 pregnant women, 118 (32%) practiced self-medication on modern medicine. The main drug categories self-used during pregnancy were B and D, considered respectively as “probably safe” and “potentially risky” for use during pregnancy according the US-FDA pregnancy risk classification. Multivariate logistic regression analysis showed that women over 30 years old were four-fold more likely to practice self-medication than the other groups [AOR: 4, 95% CI (1.74 – 9.26)]. Similarly unemployed women, multiparous, with chronic illness, without therapeutic treatment were, respectively, 3.79, 5.51, 2.76 and 9.89-fold more likely to practice self-medication than the other groups [AOR: 3.79, 95% CI (0.80 – 17.95)]; [AOR: 5.51, 95% CI (2.89– 10.47)]; [AOR: 2.76, 95% CI (1.24 – 6.14)]; [AOR: 9.89, 95% CI (2.75 – 35.51)]. Conclusion: The prevalence of modern drugs self-medication among pregnant women in Morocco is classified as lower compared to several African countries. Health professionals can exert positive pressure through education and information provided during ANC about OTC medications to significantly reduce the rate of self-medication.